1995
DOI: 10.1111/j.2042-7158.1995.tb05815.x
|View full text |Cite
|
Sign up to set email alerts
|

PEG-coated Poly(lactic acid) Nanoparticles for the Delivery of Hexadecafluoro Zinc Phthalocyanine to EMT-6 Mouse Mammary Tumours

Abstract: Hexadecafluoro zinc phthalocyanine (ZnPcF16), a second generation sensitizer for the photodynamic therapy of cancer, was incorporated in three vehicles: poly(D,L-lactic acid) (PLA) nanoparticles, polyethylene glycol (PEG)-coated nanoparticles and a Cremophor EL (CRM) oil-water emulsion. Nanoparticles were prepared by the salting-out procedure. Biodistribution of the dye was assessed by fluorescence in EMT-6 mammary tumour bearing mice after intravenous injection of 1 mumol kg-1 ZnPcF16. Plain nanoparticles wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
45
0

Year Published

1996
1996
2011
2011

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 97 publications
(51 citation statements)
references
References 26 publications
4
45
0
Order By: Relevance
“…In contrast, pegylated mTHPC revealed significantly higher concentrations compared to mTHPC in liver, spleen, heart and lung tissue at this time point. Our results suggest a difference in biodistribution of the two substances similar to that observed with pegylated and non-pegylated phthalocyanines (AllŽmann et al, 1995).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…In contrast, pegylated mTHPC revealed significantly higher concentrations compared to mTHPC in liver, spleen, heart and lung tissue at this time point. Our results suggest a difference in biodistribution of the two substances similar to that observed with pegylated and non-pegylated phthalocyanines (AllŽmann et al, 1995).…”
Section: Discussionsupporting
confidence: 73%
“…So far pegylation has mainly been applied to high molecular-weight substances such as proteins, enzymes and liposomes, but the pharmaceutical benefits may possibly be conferred upon other compounds. Other studies have shown that the uptake of pegylated phthalocyanine sensitizers in animal tumours is enhanced with increased tumour-to-skin uptake ratios compared to the nonpegylated compound (AllŽmann et al, 1995).…”
Section: Discussionmentioning
confidence: 97%
“…The Kupffer cells were identified by their active phagocytic surface morphology and by their location within the sinusoids. AuNPs were found to be accumulated in tumour-infected areas other than the normal tissues and our results are in accordance with the reports of Allemann et al [45]. …”
Section: Tissue Distribution Of Aunpssupporting
confidence: 94%
“…Thus in addition to CRM, we recently showed that ZnPcF,6 can readily be formulated in biode- gradable polyethylene glycol-coated poly(lactic acid) nanoparticles (PEG-coated PLA NP), resulting in advantageous biodistribution and excretion pattern for PDT applications (Allemann et al, 1995). Topical application of ZnPcF16 formulated in CRM also induced a good tumour response in the EMT-6 tumour model, whereas ZnPc was inactive under these conditions (Margaron et al, 1992).…”
Section: Discussionmentioning
confidence: 99%